Perancangan Ulang Interior Museum Bahari Jakarta Dengan Pendekatan Media Interaktif - Qatrunnada Salsabila Amna, Calista; Haristianti, Vika; Adrianawati, Aida (eProceedings of Art & Design, 2024)
The Jakarta Maritime Museum, established in 1718, is a cultural heritage site located in North Jakarta. Despite its historical significance, the museum's visitor numbers have declined due to a lack of interactive and engaging exhibits. This project aims to enhance the museum experience by incorporating interactive media and technology into the interior design, making it more appealing to visitors of all ages. The redesign includes creating a cohesive storyline, improving display techniques, and adding interactive elements to help visitors better understand the maritime history of Indonesia. The project methodology includes primary data collection through observations, interviews, and documentation, as well as secondary data from literature studies and precedent analyses. The expected outcome is an interactive and educational museum environment that preserves the historical integrity of the building while attracting more visitors. Keywords: Jakarta Maritime Museum, interactive media, interior redesign, visitor engagement, maritime history